Chronic Angiotensin-(1–7) Improves Insulin Sensitivity in High-Fat Fed Mice Independent of Blood Pressure. Issue 5 (May 2016) - Williams, Ian M.; Otero, Yolanda F.; Bracy, Deanna P.; Wasserman, David H.; Biaggioni, Italo; Arnold, Amy C.
Abstract : Angiotensin-(1–7) improves glycemic control in animal models of cardiometabolic syndrome. The tissue-specific sites of action and blood pressure dependence of these metabolic effects, however, remain unclear. We hypothesized that Ang-(1–7) improves insulin sensitivity by enhancing peripheral glucose delivery. Adult male C57BL/6J mice were placed on standard chow or 60% high-fat diet for 11 weeks. Ang-(1–7) (400 ng/kg per minute) or saline was infused subcutaneously during the last 3 weeks of diet, and hyperinsulinemic–euglycemic clamps were performed at the end of treatment. High-fat fed mice exhibited modest hypertension (systolic blood pressure: 137±3 high fat versus 123±5 mm Hg chow; P =0.001), which was not altered by Ang-(1–7) (141±4 mm Hg; P =0.574). Ang-(1–7) did not alter body weight or fasting glucose and insulin in chow or high-fat fed mice. Ang-(1–7) increased the steady-state glucose infusion rate needed to maintain euglycemia in high-fat fed mice (31±5 Ang-(1–7) versus 16±1 mg/kg per minute vehicle; P =0.017) reflecting increased whole-body insulin sensitivity, with no effect in chow-fed mice. The improved insulin sensitivity in high-fat fed mice was because of an enhanced rate of glucose disappearance (34±5 Ang-(1–7) versus 20±2 mg/kg per minute vehicle; P =0.049). Ang-(1–7) enhanced glucose uptake specifically into skeletal muscle by increasing translocation of glucose transporter 4 to the sarcolemma. Our data suggest that Ang-(1–7) has direct insulin-sensitizing effects on skeletal muscle, independent of changes in blood pressure. These findings provide new insight into mechanisms by which Ang-(1–7) improves insulin action, and provide further support for targeting this peptide in cardiometabolic disease. Abstract : Supplemental Digital Content is available in the text.